Kinerja Jaringan Seluler 4G LTE Operator Telkomsel & Axis di Kampus A dan C UNTIRTA - Didik Aribowo; Ina Basariyah; Daffa Abdillah Rizal; Muhammad Azmi Al-Fatih; Meylani, Putri Nazwa; Salsabila Az Zahra Fitri; Adit Mulyana; Maudi Aprianti; Yoga Angga Pratama (Pusat riset dan Inovasi Nasional, 2025)
The development of cellular communication technology has reached a significant point with the presence of 4G LTE networks, which offer high speed and spectrum efficiency. This study aims to evaluate the performance of 4G LTE networks from two operators, Telkomsel and Axis, at two locations of Sultan Ageng Tirtayasa University (UNTIRTA), namely Campus A and Campus C. The method used is a drive test with the help of the SpeedOf.me site, which measures download speed, upload speed, and latency parameters. The test results show that Telkomsel excels in upload speed with relatively good latency stability, while Axis has the advantage in the highest download speed but shows large fluctuations in performance, especially in the latency parameter. This performance variation indicates that location factors, network load, and device conditions greatly affect service quality. Overall, Telkomsel shows more stable performance, making it more reliable for network-based academic activities, while Axis is suitable for needs with a priority of download speed in optimal conditions. This study is expected to be a reference for the development of network infrastructure in higher education environments.